Cyber Crime Communication Patterns Impulsive Purchase Behavior of NCT 127 "The Unity Jakarta" Concert Tickets on X (Twitter) - Julianti, Hayati; Ainaya, Sukma; Azzahra, Tamela; Andriany, Dian (Indonesian Journal of Advanced Research, 2024)
Technological advances have changed the way humans interact and make it easier for humans to make buying and selling transactions, but behind the positive side of technology, of course, there is a negative side that can be detrimental. One of the cases that is rampant on social media (Twitter) is concert ticket fraud. The goal of the study was to identify the communication patterns that scammers engage in when selling concert tickets and understand how a person can become a victim of online fraud through the social media platform Twitter. Seven key informants of this research are victims of fraudulent ticket purchases for NCT 127 concert "The Unity Jakarta" on Twitter. The research method used is qualitative descriptive with data sources through interviews with 7 informants and observation through the Twitter accounts of the informants. This study uses the theory of Computer Mediated Communication (CMC). Based on the results of the research, the communication pattern that occurs is that fraudsters use evidence in the form of e-tickets as collateral and an excuse to sell tickets under the pretext of having excess tickets to attract the attention of victims who are in need of concert tickets. The findings indicate that the victim made a hasty purchase of concert tickets without considering the negative consequences, known as impulse buying.